Prevalence of hepatitis-C viral infection among opioid dependent injectable drug users: a study conducted at regional hospital drug de-addiction and treatment centre, Solan, Himachal Pradesh, India - Verma, Kushel; Kumar, Sanjeev; Sharma, Vaishali (International Journal of Research in Medical Sciences, 2020)
Background: There are a limited number of studies regarding the prevalence of hepatitis B, hepatitis C and HIV infections among the drug addicts in Himachal Pradesh; C virus (HCV) infection in north India especially Himachal with very high rates of substance abuse. The present study was attempted to study the prevalence of hepatitis C among the injectable drug users, which is more important in a country like India where viral hepatitis is estimated to be among the top ten causes of deaths. Methods: A study was conducted in 2019-2020 (July-April). HBsAg, anti-HBs, anti-HCV and anti-HIV tests in 235 drug addicts were studied. Urine samples obtained from drug addicts were analyzed for cannabis, opiate and cocaine metabolites. Results: The subjects included were 235 IDUs who were opioid dependent. All the 235 drug users were males, and their mean age was 30.69±9.494 years; 112 (47.7%) of them were in the age group ranging 20 - 29 years (p <0.05). Of 235 drug addicts, 113 (48.1%) and 115 (48.9%) were only cannabis and opiate users, respectively. The frequencies of HBsAg, anti-HBs and anti-HCV among drug addicts were 2.6%, 38.3%, and 9.4%, respectively. Conclusions: The obtained results showed that HCV infection was an alarming problem among opiate users in this part of Himachal. It is suggested to rapidly diagnose the infected persons; thus preventive measures and appropriate control may limit further transmission of these infections.